Perbandingan Perjanjian Pinjaman Online di Indonesia dan Amerika Serikat - Permatasari, Deshy Eka; Laurenza, Dias Prima; Azzahra, Natasya Fhadyah; Christian, Noel; Zahia, Reyna; Paradisha, Uma; Sakti, Muthia (Media Hukum Indonesia (MHI), 2024)
Currently, online loans are increasing in growth in various countries, due to the rapid growth of online loans, it is very important to understand this online loan agreement. With the growing growth of online loan services in various countries, we will therefore describe online loan agreements in Indonesia and the United States. In this article we will answer how the legal rules are applied in Indonesia and the United States in online loans and what the online loan agreement system is in Indonesia and the United States. This research uses the Normative Juridical method, which includes a legal approach that is relevant to the issue being analyzed and a Comparative Approach, namely comparing the regulations governing Online Loan Agreements in Indonesia and the United States.